Effect of Fe3+ Doping in the Photocatalytic Properties of BaSnO3 Perovskite - Moura, Kleber Figueiredo; Chantelle, Lais; Rosendo, Debora; Longo, Elson [UNESP]; Garcia dos Santos, Ieda Maria (Univ Fed Sao Carlos, Dept Engenharia Materials, 2017)
In the last ten years, stannates with perovskite structure have been tested as photocatalysts. In spite of the ability of perovskite materials to accommodate different cations in its structure, evaluation of doped stannates is not a common task in the photocatalysis area. In this work, Fe3+ doped BaSnO3 was synthesized by the modified Pechini method, with calcination between 300 and 800 degrees C/4 h. The powder precursor was characterized by thermogravimetry after partial elimination of carbon. Characterization after the second calcination step was done by X-ray diffraction, Raman spectroscopy and UV-visible spectroscopy. Materials were tested in the photocatalytic discoloration of the Remazol Golden Yellow azo dye under UVC irradiation. Higher photocatalytic efficiency was observed under acid media. As no meaningful adsorption was observed at this condition we believe that an indirect mechanism prevails. Fe3+ doping decreased the band gap and favored the photocatalytic reaction, which may be assigned to the formation of intermediate levels inside the band gap.
Keywords: Perovskite; Fe-doped; polymeric precursor method; photocatalysis; RNL